Seeking competitive advantage of farmers’ cooperatives through organizational resilience: examining the role of chairpersons’ self-efficacy and environmental dynamism - Wang, Jia; Wan, Junyi; Wu, Zhidong (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn dynamic and unpredictable environments, farmers’ cooperatives must develop organizational resilience to maintain a sustainable competitive advantage. However, the mechanisms through which resilience impacts competitiveness remain underexplored in existing literature. This study investigates how chairpersons’ self-efficacy, as a key psychological factor, fosters both planned and adaptive resilience, ultimately enhancing the cooperative’s competitive advantage.MethodsGrounded in social cognitive theory, we conducted a survey of 286 farmers’ cooperatives in Guangdong Province, China. Structural Equation Modeling (SEM) was employed to examine the relationships between self-efficacy, organizational resilience, and competitive advantage. Additionally, multiple regression analysis was used to test the moderating effect of environmental dynamism.Results and discussionThe empirical results show that chairpersons’ self-efficacy significantly strengthens both planned and adaptive resilience. In turn, these two forms of resilience positively influence cooperative competitive advantage, mediating the link between self-efficacy and competitiveness. Furthermore, environmental dynamism negatively moderates the resilience–competitiveness relationship, suggesting that resilience translates more effectively into advantage under relatively stable conditions. In highly dynamic contexts, cooperatives must complement resilience with additional adaptive strategies to sustain performance.ConclusionThis study highlights the pivotal role of chairpersons’ psychological capital in shaping cooperative resilience. By enhancing leaders’ self-efficacy, cooperatives can strengthen both planned and adaptive resilience. However, resilience yields greater benefits in stable environments, while dynamic conditions demand more flexible and adaptive approaches. These insights extend resilience theory in cooperative settings and provide practical guidance for sustaining competitiveness under uncertainty.